MR measurement of intracranial CSF volume in 41 elderly normal volunteers. - Malko, J A; Hoffman, J C; Green, R C (American Journal of Neuroradiology, 1991)
A noninvasive nonplanimetric MR protocol was used to measure the total intracranial CSF volume in 41 normal subjects, aged 60-84 years, who were intensively screened to eliminate CNS disease. The protocol entailed application of MR imaging data acquired with a spin-echo sequence in a single thick slice encompassing the head. The results show a strong correlation between increased intracranial CSF volume and increasing age, and a weaker correlation between increased intracranial CSF volume and increasing total intracranial volume. The possibility of employing a CSF volume measurement as a reflection of brain atrophy to help diagnose dementia is discussed.